Tanggung Jawab Administratif Pemerintahan Daerah dalam Pengawasan Sampah: Studi Kasus Penumpukan Sampah di Bintara Bekasi - Devina Marsela Limbong; Zahro Nurul Nabilah; Tiansi Crysti Sihotang; Dear Ayu Putri Selomita (Sociale : Journal of Social and Political Sciences, 2025)
The problem of waste accumulation in the Bintara area, Bekasi City, reflects the weak administrative responsibility of the local government in supervising waste management. This research aims to assess the form of local government responsibility in supervising waste management in accordance with applicable law. The method used in this research is normative juridical with a statutory and conceptual approach. Data was collected through a literature study of various laws, such as Law Number 23 of 2014 on Regional Government, Law Number 18 of 2008 on Waste Management, as well as regional regulations and other technical policies. The research findings show that normatively, local governments have clear responsibilities in managing and supervising waste management in their areas, but implementation is still weak due to lack of law enforcement, overlapping authority between agencies, and limited technical regulations at the local level. The study also revealed that administrative supervision has not been supported by an effective sanction mechanism as well as a lack of transparency and accountability in task implementation. In addition, the involvement of the community and private sector in waste supervision is still minimal. Local governments have also not been optimal in utilizing information technology for supervision. Therefore, there is a need to strengthen the legal aspects through harmonization of regulations, preparation of more detailed technical guidelines, capacity building of human resources, and improvement of monitoring and evaluation systems that are based on law, technology and participation.